2021
DOI: 10.1038/s43018-021-00179-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow NG2+/Nestin+ mesenchymal stem cells drive DTC dormancy via TGF-β2

Abstract: In the bone marrow (BM) microenvironment, NG2 + /Nestin + mesenchymal stem cells (MSCs) promote hematopoietic stem cell (HSC) quiescence 1,2 . Importantly, the BM can also harbour disseminated tumour cells (DTCs) from multiple cancers, which, like HSCs, can remain dormant 3 . The BM signals are so growth-restrictive that dormant BM DTCs can persist for years to decades only to awaken and fuel lethal metastasis 3-10 . The mechanisms and niche components regulating DTC dormancy remain largely unknown. Here, we r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 62 publications
9
65
0
Order By: Relevance
“…However, we did not observe any considerable change in the expression or phosphorylation of the SMAD1/5 pathway as reported for TGFβ2 24 (Figure 3a) , arguing that the AZA+atRA reprogramming may induce a canonical pathway activation. We also documented an increase in the expression of TGFβRI and TGFβRIII (Figure S4b) , both previously implicated in DCC dormancy in the BM and lung 23, 24 . Upon AZA+atRA reprogramming, we also detected a strong increase in the phosphor-p38 and p27, while P-Erk1/2 or total Erk1/2 remained constant, leading to a low ERK/p38 activity ratio 14, 32 (Figure 3a) .…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…However, we did not observe any considerable change in the expression or phosphorylation of the SMAD1/5 pathway as reported for TGFβ2 24 (Figure 3a) , arguing that the AZA+atRA reprogramming may induce a canonical pathway activation. We also documented an increase in the expression of TGFβRI and TGFβRIII (Figure S4b) , both previously implicated in DCC dormancy in the BM and lung 23, 24 . Upon AZA+atRA reprogramming, we also detected a strong increase in the phosphor-p38 and p27, while P-Erk1/2 or total Erk1/2 remained constant, leading to a low ERK/p38 activity ratio 14, 32 (Figure 3a) .…”
Section: Resultssupporting
confidence: 69%
“…We observed that all three SMADs are, as expected, low in malignant T-HEp3 cells, and AZA+atRA treatment caused a significant increase in the total expression level of SMAD2, SMAD3, and SMAD4 (Figure 3a) . We had published that TGFβ2 induced DCC dormancy in the bone marrow via an activated P-p38 as well as SMAD2 and SMAD1/5 pathway, which induced expression of p27 leading to quiescence 23, 24 . Upon AZA+atRA reprogramming, we observed an increase in the mRNA levels of TGFβ2 14 , along with TGFβ1 and TGFβ3 ( Figure S4a) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer-induced bone changes seem to take place when DCCs reactivate and during the proliferation period. Specifically, reactivated DCCs can lead to the differentiation of osteoclastic precursors and fuel the process of osteolytic metastasis [ 33 , 34 , 35 ]. In contrast, the interplay between dormant cells and cellular components of bone appears to favor osteoclasts and osteoblasts working in a balanced manner, similar to that of a healthy individual.…”
Section: Dormancy In Prostate Cancermentioning
confidence: 99%
“…Periarteriolar BM-resident NG2+/nestin+ MSCs guide BCa DCCs to enter dormancy by producing TGFβ2 and bone morphogenetic protein (BMP7), which activates a quiescence pathway dependent on TGFFBRIII and BMPRII. Depletion of the NG2+/nestin+ MSCs or knockout (KO) of TGFβ2 specifically from NG2+/nestin+ MSCs leads to metastatic outgrowth in BM [ 33 ].…”
Section: Niche Cell Types and Signals That Induce Or Block Pca DCC Dormancy In The Bone Marrow Microenvironmentmentioning
confidence: 99%